We are all Human Beings - Lepp Friesen, Helen (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2022)
This article describes a teacher’s journey into prison where she delivers university writing classes. The author explores techniques and strategies that foster empowerment in prison classrooms. Based on the author’s experience and secondary research on critical pedagogy and transformative learning, she explores what it means to treat university writing students in prison like human beings and how to inspire emotionally and socially engaged learning.